Peran Hukum Islam dalam Menyikapi Pernikahan Beda Agama : Harmonisasi dan Konflik dalam Konteks Global - Dina Agustian; Nesa Pebiola; Novi Fitriani; Putri Padilah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Interfaith marriage is a complex issue with far-reaching legal, religious and social implications. This research analyzes the role of Islamic law in addressing interfaith marriage, focusing on the dynamics between harmonization and conflict. Through a literature review and survey, this research identifies the factors that influence the acceptance or rejection of interfaith marriage from an Islamic perspective. According to the questionnaire survey results, the majority of respondents rejected interfaith marriage absolutely, reflecting the strong traditional views in the Muslim community. However, there are also groups that allow these marriages under certain conditions, such as one of the couple converting. This shows the plurality of views in Islamic society regarding the issue of interfaith marriage. This shows the dynamics between religious norms and complex social realities in the context of interfaith marriage globally. Although Islamic law generally prohibits interfaith marriage, social practice shows that there are variations in its application.